(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
This research includes a monitoring and an evaluation of the air pollution levels generated by the re-suspended and airborne dust due to traffic movement at the main busy crossroads of Hilla City, Nader Crossroad and Al-Thowra Crossroad, Iraq. The re-suspended dust is one of the most important contributors towards overall atmospheric pollution, especially when the roads are unpaved or under maintenance with high traffic load such as Nader Crossroad, which was under maintenance to construct a bridge on it. The concentrations of the total suspended particulate matters were determined at the two locations using portable air sampler during traffic rush hour on sunny moderated weekdays for four months, December 2011, February 2012, April 2012, and May 2012. The results have confirmed the contribution of the unpaved roads in air pollution. The results showed that the average TSP levels at Nader Crossroad was higher than the average TSP levels at Al-Thowra Crossroad during the total period of the study in which the minimum TSP level at Nader Crossroad was 5676.67 μg/m3, which was higher than the maximum TSP level at Al-Thowra Crossroad, 4096.41 μg/m3. In addition, the re-suspended dust concentrations that were measured in this study and ranged from 426.06 to 9348.95 μg/m3 are much higher than the American Environmental Protection Agency acceptable limits of national ambient air quality standards for the particulate matter.